Characterisation of liver fat in the UK Biobank cohort - Wilman,HR; Kelly,M; Garratt,S; Matthews,PM; Milanesi,M; Herlihy,A; Gyngell,M; Neubauer,S; Bell,JD; Banerjee,R; Thomas,EL (PLOS ONE, 2017)
Non-alcoholicfattyliverdiseaseandtheriskof progressionto steatohepatitis,cirrhosisandhepatocellularcarcinomahavebeenidentifiedasmajorpublichealthconcerns.Wehavedemonstratedthefeasibilityandpotentialvalueof measuringliverfatcontentbymagneticresonanceimaging(MRI)in a largepopulationin thisstudyof 4,949participants(aged45–73years)in theUKBiobankimagingenhancement. Despiterequirementsforonlya single( 3min)scanof eachsubject,liverfatwasableto bemeasuredastheMRIprotondensityfatfraction(PDFF)withanoverallsuccessrateof 96.4%.Theoverallhepaticfatdistributionwascentredbetween1–2%,andwashighlyskewedtowardshigherfatcontent.ThemeanPDFFwas3.91%,andmedian2.11%.Analysisof PDFFin conjunctionwithotherdatafieldsavailablefromtheUKBiobankResourceshowedassociationsof increasedliverfatwithgreaterage,BMI,weightgain,highbloodpressureandType2 diabetes.SubjectswithBMIlessthan25kg/m2hada lowrisk(5%)of highliverfat(PDFF>5.5%),whereasin thehigherBMIpopulation(>30kg/m2) theprevalenceof highliverfatwasapproximately1 in 3. Thesedatasuggestthatpopulationscreeningto identifypeoplewithhighPDFFis possibleandcouldbecosteffective.MRIbasedPDFFis aneffectivemethodforthis.Finally,althoughcrosssectional,thisstudysuggeststheutilityof thePDFFmeasurement withinUKBiobank,particularlyforapplicationsto elucidatingriskfactorsthroughassociationswithprospec-tivelyacquireddataonclinicaloutcomesof liverdiseases,includingnon-alcoholicfattyliverdisease.